Association of Histones With Coagulofibrinolytic Responses and Organ Dysfunction in Adult Post-cardiac Arrest Syndrome - Mizugaki, Asumi; Wada, Takeshi; Tsuchida, Takumi; Gando, Satoshi (Frontiers in Cardiovascular Medicine, 2022)
Patients successfully resuscitated from cardiac arrest often develop organ dysfunction caused by systemic inflammation and increased coagulation, leading to disseminated intravascular coagulation (DIC). The involvement of histones in DIC and organ dysfunction in patients with sepsis and trauma has been previously reported, raising the probability that histones may also be associated with pathophysiology in patients after cardiac arrest and resuscitation. This study evaluated the relationship between histones and organ dysfunction related to coagulofibrinolytic changes in patients with post-cardiac arrest syndrome (PCAS). Methods: This prospective single-center observational study assessed 35 adult patients with PCAS who were divided into two groups, i.e., 15 patients with multiple organ dysfunction syndrome (MODS) and 20 patients without MODS. MODS was defined as a sequential organ failure assessment score of ≥12. The plasma levels of histones and coagulofibrinolytic markers, including soluble fibrin, plasmin-alpha 2-plasmin inhibitor complex (PIC), plasminogen activator inhibitor-1, soluble thrombomodulin, and tissue-type plasminogen activator, were measured in patients with PCAS immediately after admission to the emergency department, and 3 and 24 h after arriving at the hospital. Results: PCAS patients with MODS had higher DIC scores (4 (3.0–5.0) vs. 1 (0.0–3.0), p = 0.012) and higher mortality rates (66.7% vs. 20.0%, p = 0.013) than those without MODS. Moreover, patients with MODS exhibited higher histone levels than those without MODS during the early phase of the post-resuscitation period. Severe endothelial injury and higher thrombin and plasmin generation were observed in the MODS group. Plasma levels of histones were positively correlated with those of soluble fibrin immediately after resuscitation (rho = 0.367, p = 0.030) and PIC 3 h after arriving at the hospital (rho = 0.480, p = 0.005). This correlation was prominent in the patient population with MODS (soluble fibrin: rho = 0.681, p = 0.005, PIC: rho = 0.742, p = 0.002). Conclusions: This study demonstrated that elevated histone levels were associated with increased levels of thrombin, and subsequent plasmin generation in PCAS patients, especially those with MODS. Further studies are required to elucidate the causal relationship between histones and organ dysfunction related to DIC in PCAS.